Venous thromboprophylaxis after total hip arthroplasty: aspirin, warfarin, enoxaparin, or factor Xa inhibitors?. Issue 5 (September 2020) - Bala, Abiram; Murasko, Marlon J; Burk, David R; Huddleston, James I; Goodman, Stuart B; Maloney, William J; Amanatullah, Derek F
Introduction: Debate over the ideal agent for venous thromboembolism (VTE) prophylaxis after total hip arthroplasty (THA) has led to changes in prescribing trends of commonly used agents. We investigate variation in utilisation and the differences in VTE incidence and bleeding risk in primary THA after administration of aspirin, warfarin, enoxaparin, or factor Xa inhibitors. Methods: 8829 patients were age/sex matched from a large database of primary THAs performed between 2007 and 2016. Utilisation was calculated using compound annual growth rate. Incidence of postoperative deep venous thrombosis (DVT), pulmonary embolism (PE), bleeding-related complications, postoperative anaemia, and transfusion were identified at 2 weeks, 30 days, 6 weeks, and 90 days. Results: Aspirin use increased by 33%, enoxaparin by 7%, and factor Xa inhibitors by 31%. Warfarin use decreased by 1%. Factor Xa inhibitors (1.7%) and aspirin (1.7%) had the lowest incidence of DVT followed by enoxaparin (2.6%), and warfarin (3.7%) at 90 days. Factor Xa inhibitors (12%) and aspirin (12%) had the lowest incidence of blood transfusion followed by warfarin (15%) and enoxaparin (17%) at 90 days. There was no difference in incidence of blood transfusion or bleeding-related complications nor any detectable difference in symptomatic PE incidence. Conclusions: The utilisation of aspirin and factor Xa inhibitors increased over time. Aspirin and factor Xa inhibitors provided improved DVT prophylaxis with lower rates of postoperative anaemia compared to enoxaparin and warfarin.